MSC Multimedia Super Corridor (Kuala Lumpur : [s.n.] ; Kuala Lumpur : Multimedia Development Corporation [distributor])
Located the hub of Asia's fastest growing markets, Malaysia's Multimedia Super Corridor (MSC) is a bold initiative - a regional launch site for companies developing or using leading multimedia technologies